Genome Characterization of Lactiplantibacillus plantarum Strain UTNGt2 Originated from Theobroma grandiflorum (White Cacao) of Ecuadorian Amazon: Antimicrobial Peptides from Safety to Potential Applications - Gabriela N. Tenea; Clara Ortega (MDPI AG, 2021)
The genome characterization of the Lactiplantibacillus plantarum strain UTNGt2, isolated from wild copoazu or white cacao (Theobroma grandiflorum), is described. A total of 31 contigs is assembled with a total length of 3,264,448 bases, with all contigs matching the core genome of different groups in the database. The genome size is 3,540,752 bases with GC content of 44.53% and the genome repeat sequences constitute around 457,386 bases of the assembly. The UTNGt2 matches the Lactiplantibacillus plantarum genome with 99% identity. The genome contains 3115 genes, 3052 protein-coding genes, assigned with the EggNOG database. On the basis of the results, 745 proteins are classified with an unknown function, from which 128 proteins have no match in the BLASTN database. It also contains 57 tRNAs, 5 copies of 5S rRNA, and 1 copy of tmRNA. Based on gene prediction and annotation results, 9.4% of proteins are involved in carbohydrate transport and metabolism and 8.46% in transcription, 2.36% are responsible for defense mechanisms, 0.5% are responsible for the biosynthesis of secondary metabolites, transport, and catabolism, while 25.11% have an unknown function. The genome revealed the presence of genes involved in riboflavin and folate production, the presence of CRISPR/Cas genes, phage sequences, the absence of acquired antibiotics resistance genes, virulence, and pathogenic factors, suggesting that UTNGt2 is a safe strain. Its highly antimicrobial capacity is related to the presence of two bacteriocin clusters (class IIc) of the sactipeptide class (contig 4) and plantaricin E class (contig 22), as detected by the BAGEL 4 webserver. Several RiPP-like peptides (non-bactericidal ribosomally produced and post-translationally modified peptides), polyketides (PKs), and terpenes were predicted. Whole-genome sequencing analysis revealed that the UTNGt2 strain has diverse bacteriocins with a high inhibitory capacity, thus it is a bacteriocinogenic strain. Considering the safety profile, UTNGt2 is a nonpathogenic, nonvirulent strain with valuable biotechnological traits and can be further exploited for its probiotic and antimicrobial potential in the food industry or as a potential producer strain of antimicrobial peptides as an alternative to conventional antibiotics.